THE EFFECT OF AL-QUR'AN MUROTTAL THERAPY ON CHANGES PREOPERATIVE PATIENTS ANXIETY LEVELS AT RSUD KOTA BOGOR: PENGARUH TERAPI MUROTTAL AL-QUR’AN TERHADAP PERUBAHAN TINGKAT KECEMASAN PADA KLIEN PRE-OPERATIF DI RSUD KOTA BOGOR - Tisna Tisna Yanti; Retno Retno Dwi Shanti (Jurnal Ilmiah Wijaya, 2019)
Anxiety is a disorder of feeling (affective) that is characterized by worries or fears that are excessive and often irrational. The World Health Organization (WHO), the proportion of the global population with anxiety disorders in 2015 is estimated at 3.6%. The estimated total number of people living with anxiety disorders in the world is 264 million. The results of mental health Riskesdas in Indonesia, West Java, have 9.3% of 703,946 people in all provinces in the prevalence of mental emotional disorders. Bogor city is the largest (28.1%).Women's mental emotional disorders were 11.6% higher than 7.0% men in the population aged 15years and above.This study aims to determine the effect of murottal Al-Qur'an therapy on changes in anxiety levels in preoperative clients in Bogor City Hospital in 2019. This type of research is an experiment with a design Quasy experiment with Pre Test and Post Test Non-equivalent Control Group Design. The population of this study were all pre-operative patients in the Dahlia Room of the Bogor City Hospital, with a sample of 32 respondents using the Non-Random with Purposive Sampling technique, and data collection using a questionnaire at the preliminary study stage and questionnaire sheet at the research stage.It shows that there are differences in the scale of anxiety change before and after in the intervention group of 0,000, in addition, there are differences in the scale of anxiety change before and after in the control group of 0,051, and there is an effect of murottal Al-Qur'an therapy on changes in anxiety levels in pre-operative clients at Bogor City Hospital for 0,000 (P <0.05).There is an effect of murottal Al-Qur’an therapy on changes in anxiety levels in pre-operative clients at Bogor City Hospital in 2019. From the results of this study it is expected to be input for pre-operative clients to reduce anxiety levels.